Using the Property of Equality, what first step would you take to rearrange the formula y=mx+b using x as the quantity of interest?(1

1 answer

To rearrange the formula \( y = mx + b \) to solve for \( x \), you'll want to isolate \( x \) on one side of the equation. Here are the steps using the Property of Equality:

  1. Subtract \( b \) from both sides:
    \[ y - b = mx \]

  2. Divide both sides by \( m \) (assuming \( m \neq 0 \)):
    \[ \frac{y - b}{m} = x \]

Thus, the rearranged formula to solve for \( x \) would be:
\[ x = \frac{y - b}{m} \]